Psychological skills, mental toughness and anxiety in elite handball players - Kristjánsdóttir, H.; Erlingsdóttir, A. V.; Sveinsson, G.; Saavedra, J. M. (Personality and Individual Differences, 2018)
The objectives of this study were: to analyse psychological skills, mental toughness, and anxiety in elite handball players as functions of category (age group) and sex, and to develop a multivariate model explaining handball performance from a psychological perspective. One hundred and seventy four handball players (18.8 ± 3.5 years), components of the national teams, participated in the study. They were classified into official categories (age groups). Three questionnaires were used: the Test of Performance Strategies Questionnaire, the Sport Mental Toughness Questionnaire, and the Sport Anxiety Scale-2 questionnaire. A one-way ANOVA with Bonferroni post-hoc correction was used to examine differences between teams for each sex. A discriminant analysis was performed for each team to classify the participants into two groups according to their performance level (starters and non-starters). The results showed there to be no differences in the variables studied as a function of age. However, men reported lower anxiety than women. The discriminant analysis correctly classified high percentages of the players (65.2% to 100%). In the younger players, the variables selected were related to mental toughness and anxiety. For the men's and women's A Teams the most discriminating variables were emotional control in practice and relaxation in competition, respectively.